TOWARDS ACHIEVING ZERO WASTAGE MATERIAL IN CONSTRUCTION INDUSTRY - Irma Hanie Ibrahim; Najlaa Insyirah Binti Jamaludin; Edelin Hussein; Ts Sr Wan Mohd Nurdden Wan Muhammad (Jurnal Penyelidikan Sains Sosial, 2023)
Construction industry is seen as a profit-oriented industry especially in Malaysia, as it gives positive impact towards the economy of a country. However, a massive amount of construction waste material is resulted through the rising number of construction and demolition activities. A substantial amount of waste is generated at all phases of construction from site preparation to demolition of existing structures to its final product. Therefore, the aim of this study is to accelerate the transition from a severe waste problem to zero construction waste in the Malaysian Construction Industry. In order to achieve the aim of this research, this study is specifically emphasized on the current waste handling practices, the challenges that have prevented Malaysia from implementing this proposed concept into practice and provide industry-wide solutions needed to achieve zero material waste. A quantitative approach is used to obtain data in which a set of questionnaires require construction industry players to respond. The result indicates that construction practitioners are aware with the current waste situation, but it still needs improvement as seen by the data collected, which demonstrates that this concept has numerous benefits for both the construction industry and environment. On the basis, the zero-waste concept should be taken into account for every construction project and in-depth plan is necessary for the implementation of this concept to be successful. This study will also assist industry experts better understanding and support the zero construction waste practises in Malaysia.